(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
In this article includes it should be said that communication between people is carried out through the means of communication texts (and this is recognized by the creators of text linguistics, in general, by the majority of text researchers), limiting the text only to the written form contradicts the existing rules of text theory. After all, it is impossible to imagine that any communication between people takes place only and only in written form.